Sociodemographic and clinical characteristics of patients with conversion disorder in Eastern Turkey - Kuloglu, M; Atmaca, M; Tezcan, E; Gecici, O; Bulut, S (Springer Heidelberg, 2003)
Background: Conversion disorder (CD) is a common disease and its importance still continues in Turkey and particularly in Eastern Turkey. The aim of this study is to examine sociodemographic and clinical characteristics of CD. Method Among 198 consecutive patients having CD diagnosed by structured DSM-III-R clinical interview, the psychosocial characteristics of the patients were clinically investigated. Results The most common subtype of CD was non-epileptic seizure (NES) (41.4 %). The psychosocial stress factors were found in the initiation or at the last episode of the disorder (88.9 %). The most prominent problem related with primary support group was traumatic event (37.9 %) followed by problems associated with migration and related economical problems which are the most important problems of the study area. The incidence of depressive disorders was high in patients with CD, and the histrionic personality disorder was the most prominent personality pathology among the patients. Direct referral to psychiatry clinics appeared to be low (12.1 %). Conclusion Our findings have shown that traumatic events may have an important role in the occurrence, severity and duration of CD, and most of the patients seek help from religious healers. The study has also revealed that lower education level and socioeconomic and sociocultural problems may play a role in the occurrence of the disorder as well as regarding its course.
Keywords: conversion disorder; sociodemographic; non-epileptic seizure; epidemiology; traumatic event